1991
DOI: 10.1210/endo-129-6-3009
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Norepinephrine in the Control of Puberty in the Female Rhesus Monkey,Macaca Mulatto*

Abstract: The onset of puberty in female rhesus monkeys is characterized by increases in pulsatile LHRH release. In this study we have tested the hypothesis that changes in input to the LHRH neurosecretory system from noradrenergic neurons contribute to this pubertal increase in LHRH release. In the first experiment, the ability of the LHRH neurosecretory system of prepubertal (12-20 months of age, no signs of puberty evident), early pubertal (24-30 months, premenarchial), and midpubertal (30-45 months, postmenarchial b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 31 publications
5
21
0
Order By: Relevance
“…Since we have found that excitatory inputs from norepinephrine and neuropeptide Y neurons to LHRH neurons are contributing factors for the pubertal increase in LHRH release (26,34), and since others have shown that stimulation of N-methyl-D-aspartate receptors results in precocious puberty (35,36) detailed studies are required to clarify the regulation of LHRH release by other neurotransmitters during puberty.…”
Section: Resultsmentioning
confidence: 97%
“…Since we have found that excitatory inputs from norepinephrine and neuropeptide Y neurons to LHRH neurons are contributing factors for the pubertal increase in LHRH release (26,34), and since others have shown that stimulation of N-methyl-D-aspartate receptors results in precocious puberty (35,36) detailed studies are required to clarify the regulation of LHRH release by other neurotransmitters during puberty.…”
Section: Resultsmentioning
confidence: 97%
“…First, the immunoreactive and biologically active content of LHRH is similar in pre pubertal and adult rhesus monkeys [4]. Second, neither the abundance of LHRH mRNA per cell nor the number of LHRH mRNA-containing cells, measured by in situ hybridization, differ between prepubertal and adult ani mals [5], Lastly, administration of either a r adrcncrgic agonists [6], a GABA-A receptor antagonist [7] or Nmethyl-D-aspartic acic [8], an N-methyl-D-aspartic acid receptor agonist, elicits LHRH release in juvenile mon keys, indicating that prepubertal LHRH neurons are per fectly capable of responding to changes in neurotransmit ter inputs with LHRH release. Based on these findings it would appear reasonable to postulate that the initiation of primate puberty is determined by 'upstream' events which presumably occur in cellular subsets anatomically and/or functionally connected to the LHRH neuronal net work [9], While the molecular basis of these events has not been elucidated, an obvious consequence of their occur rence appears to be a change in neuronal activity that leads to alterations in the excitatory/inhibitory transsynaptic control of LHRH neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these findings it would appear reasonable to postulate that the initiation of primate puberty is determined by 'upstream' events which presumably occur in cellular subsets anatomically and/or functionally connected to the LHRH neuronal net work [9], While the molecular basis of these events has not been elucidated, an obvious consequence of their occur rence appears to be a change in neuronal activity that leads to alterations in the excitatory/inhibitory transsynaptic control of LHRH neurons. The concerted effect of these alterations may, in turn, result in activation of LHRH release [6,7,10], While the importance of this transsynaptic control of LHRH neuronal function appears clear, we have raised the possibility of a glial involvement in the neuroendocrine process controlling the activation of LHRH neurons at puberty [10,11], In contrast to the scant innervation received by LHRH neurons in the primate hypothalamus [ 12], glial ensheathment of both LHRH neuronal perikarya and LHRH nerve terminals is substantial [12], suggesting the existence of meaningful interactions between the two cell types. That glial cells may affect LHRH secretion via secretion of defined bioactive molecules has been suggest ed by a series of experiments in rodents implicating hypo thalamic transforming growth factor alpha (TGFa) [ 13] of glial origin [11] in the regulatory process by which the hypothalamus controls the advent of normal sexual matu ration [11,14] and by which hypothalamic lesions induce sexual precocity [15,16], Whether TGFa, and hence glial cells, also contributes to the inititation of primate puberty is not knwon.…”
Section: Introductionmentioning
confidence: 99%
“…Because the GnRH neurosecretory system is already morphologically and functionally mature long before the onset of puberty Goldsmith and Song, 1987), it is probable that changes in inputs to the GnRH system are responsible for the increase in pulsatile GnRH release that ultimately results in the attainment of adult reproductive function. For example, increases in stimulatory inputs from noradrenergic (Advis et al, 1978;Raum et al, 1980;Gore and Terasawa, 1991), neuropeptide Y (Sutton et al, 1988;Minami et al, 1990;Gore et al, 1993;Gruaz et al, 1993), and glutamatergic (Gay and Plant, 1987;Urbanski and Ojeda, 1990) neurons precede the onset of puberty. Similarly, a decrease in inhibition from GABAergic neurons probably also contributes to the timing of puberty (Mitsushima et al, 1994).…”
mentioning
confidence: 99%